2005
DOI: 10.1029/2004gl021671
|View full text |Cite
|
Sign up to set email alerts
|

A measure of near‐surface fluid motions that predicts air‐water gas transfer in a wide range of conditions

Abstract: A measure of near-surface fluid motions that predicts air-water gas transfer in a wide range of conditions Conceptual Model 75[4] The gas transfer coefficient, k, is defined as and convective liquid motions control the gas transfer rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 26 publications
6
51
1
Order By: Relevance
“…Moreover, the study of Banerjee et al (2004) found that the surface divergence model can be applied to sheared free surfaces, which is supported by the simulations of Lakehal et al (2008a) and Lakehal, Fulgosi & Yadigaroglu (2008b). This observation is also verified in the experimental work of Turney, Smith & Banerjee (2005) with A being 0.45 and in the recent numerical simulation of Hasegawa & Kasagi (2009) with A being 0.40 for Sc of 1 and 100.…”
Section: Results Overview and Validationsupporting
confidence: 69%
“…Moreover, the study of Banerjee et al (2004) found that the surface divergence model can be applied to sheared free surfaces, which is supported by the simulations of Lakehal et al (2008a) and Lakehal, Fulgosi & Yadigaroglu (2008b). This observation is also verified in the experimental work of Turney, Smith & Banerjee (2005) with A being 0.45 and in the recent numerical simulation of Hasegawa & Kasagi (2009) with A being 0.40 for Sc of 1 and 100.…”
Section: Results Overview and Validationsupporting
confidence: 69%
“…KG04; Turney et al 2005) and numerical studies (e.g. Handler et al 2003;Shen et al 2004;Magnaudet & Calmet 2006;Khakpour et al 2011) have confirmed that the surface divergence is a good measure for the transfer velocity as the surface condition is implicitly taken into account.…”
Section: Significant Reduction Of K Lmentioning
confidence: 90%
“…Osborne (1965) presented a theory to describe the modulation of the skin temperature by waves and other flows that generate a straining flow in the skin layer. Surface straining models have also been used to describe the heat and gas transfer due to subsurface turbulence, by parameterizing the straining flow generated by turbulent eddies (e.g., Fortescue and Pearson 1967;McKenna and McGillis 2004;Turney et al 2005). A surface straining model was also applied by Csanady (1990) to predict the gas transfer due to high vorticity wavelets.…”
Section: Introductionmentioning
confidence: 99%